2009
DOI: 10.1002/aoc.1516
|View full text |Cite
|
Sign up to set email alerts
|

2‐Pyridylquinoxaline derivatives as N,N‐ligands for palladium‐catalyzed Suzuki–Miyaura reaction

Abstract: The Suzuki-Miyaura reaction of aryl bromides with benzeneboronic acid catalyzed by bis(chloro)(2-pyridylquinoxaline)palladium(II) was investigated. The scope of the bis(chloro)(2-pyridylquinoxaline)palladium(II) was determined in toluene at 80• C using KOH as base. Using a 0.1% molar ratio of bis(chloro)(2-pyridylquinoxaline)palladium(II) C1 as a catalyst, aryl bromides reacted with benzeneboronic acid to afford diaryl derivatives in excellent yield.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 49 publications
0
4
0
Order By: Relevance
“…As such conversions are reported only for complexes with chloride and not azide as coordinated anion, so the chloro derivatives are chosen. It is found that the catalytic activity of 3 is comparable to IV , Va and Vb in the coupling involving aryl bromides though these complexes are less bulky as compared to 3 , and moreover Va and Vb are water soluble ionic complexes ,. Further, complex IV has not been explored coupling reactions involving chloro substrates whereas Va and Vb show poorer activity than 3 for the same couplings.…”
Section: Resultsmentioning
confidence: 99%
“…As such conversions are reported only for complexes with chloride and not azide as coordinated anion, so the chloro derivatives are chosen. It is found that the catalytic activity of 3 is comparable to IV , Va and Vb in the coupling involving aryl bromides though these complexes are less bulky as compared to 3 , and moreover Va and Vb are water soluble ionic complexes ,. Further, complex IV has not been explored coupling reactions involving chloro substrates whereas Va and Vb show poorer activity than 3 for the same couplings.…”
Section: Resultsmentioning
confidence: 99%
“…However, K 2 CO 3 showed the best result with 95% yield ( Table 3, entry 12). The reaction was also carried out at different temperatures (25,40,60,80, and 100 C) and the best result was obtained at 60 C ( Under the optimized conditions, the Suzuki reaction was carried out on various aryl halides and the results are summarized in Table 4. Aryl bromides and aryl iodides containing electron-withdrawing or electrondonating groups were successfully reacted and the corresponding products were obtained in excellent yields.…”
Section: Investigation Of Catalyst Activity (Mnp@pgma@dap@au) In Sumentioning
confidence: 99%
“…[20][21][22] The Suzuki-Miyaura reaction is usually performed by palladium catalyst. [23][24][25][26] Ni and Cu catalysts have also been used for this reaction but they have low yields. [27,28] Au catalysts have also exhibited high catalytic activity in the Suzuki reaction.…”
Section: Introductionmentioning
confidence: 99%
“…[2][3][4][5][6][7][8] Moreover, palladium-mediated organic synthesis is also extended to the reactions of Sonogashira-Hagihara 9,10 and Suzuki-Miyaura. [11][12][13][14] In order to improve the catalytic efficiency of the palladium system, various complexes have been developed and indications into the electronic and steric influences exerted by the nature of the substituents on the ligands employed have been reported. [15][16][17] Moreover, some palladium complex pre-catalysts could promote the coupling reaction of less active haloarenes or alkenes.…”
Section: Introductionmentioning
confidence: 99%